HUBUNGAN KEGIATAN CUSTOMER RELATIONS INDOSAT DENGAN KEPUASAN PENGGUNA BLACKBERRY - Panjaitan, Ferdina Elizabeth Hasiholan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2012)
The reason for choosing the formation of brand image with user satisfaction Indosat Blackberry is Blackberry users want to know how the University Prof. Dr. Moestopo using Indosat as the operator, which serves as the brand image Indosat in Indonesia to facilitate Blackberry. In this study the authors used information theory to explain how the message can act to connect the participants in the communicative process. Expectancy theory (expectation value) to explain how the behavior is generally more influenced by the hope of achieving something desired results (no positive incentives) rather than by a boost in self-expectation of value is based on the balance of trust and evaluation. Customer satisfaction theory theory that measures the level of satisfaction or level of humane feelings arise, which was appreciated by friendliness, familiarity, polite and appreciative customers by providing services and information in accordance with ones expectations of performance / achievement (outcome).